Menghindari Green Marketing Myopia: Upaya Peningkatan Performa Produk Ramah Lingkungan - Berta Bekti Retnawati (Conference In Business, Accounting, And Management (CBAM), 2012)
In practice, green appeals are not likely to attract mainstream consumers unless they also offer a desirable benefit. To avoid green marketing myopia, marketers must fulfill consumer needs and interest beyond what is good for the environment. The Three Cs of consumer value position, calibration of consumer knowledge, and credibility of product claims are three important principles to avoid green marketing myopia. Third parties with respected standards for environmental testing and Eco- sertificationsÂ can help to clarify and bolster the believability of product claims.Â Keywords: Green marketing myopia, three Cs.